Dynamics of myosin, microtubules, and Kinesin-6 at the cortex during cytokinesis in Drosophila S2 cells. - Vale, R.D.; Spudich, J.A.; Griffis, E.R. (Journal of Cell Biology, 2009)
Signals from the mitotic spindle during anaphase specify the location of the actomyosin contractile ring during cytokinesis, but the detailed mechanism remains unresolved. Here, we have imaged the dynamics of green fluorescent protein-tagged myosin filaments, microtubules, and Kinesin-6 (which carries activators of Rho guanosine triphosphatase) at the cell cortex using total internal reflection fluorescence microscopy in flattened Drosophila S2 cells. At anaphase onset, Kinesin-6 relocalizes to microtubule plus ends that grow toward the cortex, but refines its localization over time so that it concentrates on a subset of stable microtubules and along a diffuse cortical band at the equator. The pattern of Kinesin-6 localization closely resembles where new myosin filaments appear at the cortex by de novo assembly. While accumulating at the equator, myosin filaments disappear from the poles of the cell, a process that also requires Kinesin-6 as well as possibly other signals that emanate from the elongating spindle. These results suggest models for how Kinesin-6 might define the position of cortical myosin during cytokinesis.